Short-term fluctuations in bivalve larvae compared with some environmental factors in a coastal lagoon (South Portugal) - Chícharo, Luís (2013)
In this study, short-term fluctuations in bivalve larvae were compared with some triggering factors for a period of sixteen months. Data on the abundance of planktonic larvae, collected two to three times a week were related to water temperature, salinity, wind velocity, tidal amplitude and chlorophyll a. Higher densities of planktonic bivalve larvae were caught between May and August, but intense fluctuations in abundance were observed. Planktonic bivalve larvae of eighteen taxa were identified. Larvae of Mytilus galloprovincialis, Cerastoderma edule, Ruditapes decussates and Venerupis spp. were the most abundant. The seasonal fluctuations of bivalve abundance seem to be controlled by temperature, the major factor in the timing of the reproduction of bivalves. Nevertheless, advection may be also a key factor during the planktonic life of bivalve species in coastal systems, such as the Ria Formosa.